TINJAUAN TENTANG DAYA TAHAN PADA ATLET TAKRAW PUTRI RIAU - Sopri Yanti; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the observations that have been done by the author at the Riau Provincial Princess at the time of training and at the time of the match, the author sees and encounters some problems that is: the fatigue of the athlete in doing the exercises and the game so that the exercise is not maximal, no flexibility or not fast moving athlete moving places due to excessive fatigue so that the movement is less than the maximum, so it can easily be defeated by his opponent. The purpose of this study is to find out how much endurance athletes takraw daughter Riau Province government. population in this research is athletes takraw daughter of Riau Province government amounting to 12 people. the sample in this study amounted to 12 people. However, considering that the population is small then this research is all the population is sampled (total sampling). The instruments used in this study were a 200-meter run and a 15-minute run. The results of aerobic endurance variable data by running 15 minutes, it turns out that from 12 athletes takraw daughter of Riau Province, 7 female samples have score value 39,20-44,10 (Less category) with percentage 58,33%, and 5 people (Less category) with a percentage of 41.67%, then in the category (Moderate, Good, Very Good) 0%. It can be said that the endurance capability of Riau Province women takraw athletes 100% Low or Not maximal category. Furthermore, data taken from anaerobic ability ie run 200 meters, from 12 female athlete, 11 female sample have score value <60,02 (Good One category) with percentage 91,67%, and 1 person (Less Purname category) with percentage of 8.33%, then in the category (moderate, good, and less) 0%. It can be said that the endurance ability of aerobic athlete takraw daughter of Riau Province 100% good category or maximal already. Keywords: Endurance, Takraw, Women Riau Atlet